2013
DOI: 10.1016/j.athoracsur.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Head Computed Tomography Imaging in the Evaluation of Postoperative Neurologic Deficits in Cardiac Surgery Patients

Abstract: Background Computed tomography(CT) scans of the head without contrast are routinely obtained to evaluate neurologic deficits after cardiac surgery(CS), but their utility is unknown. We evaluated our experience with this imaging modality to determine its value. Methods We retrospectively identified CS patients with postoperative neurologic deficits occurring during the first week after surgery between January 2000 and December 2012. Stroke was defined by neurologist’s determination, while a non-focal deficit(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The incidence of neurological deficits following CS varies from 25% to 79% while 6% comprises of FD [6][7][8][9][10][11][12][13][14][15][16][17]. In the study by Beaty et al the incidence of NC in early POP of post CS patient was 6.1% [18]. In our study the incidence of NC in the early POP of CS patients was 6.7% and thus our findings corroborate those of Beaty and colleagues.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The incidence of neurological deficits following CS varies from 25% to 79% while 6% comprises of FD [6][7][8][9][10][11][12][13][14][15][16][17]. In the study by Beaty et al the incidence of NC in early POP of post CS patient was 6.1% [18]. In our study the incidence of NC in the early POP of CS patients was 6.7% and thus our findings corroborate those of Beaty and colleagues.…”
Section: Discussionsupporting
confidence: 82%
“…Beaty et al found the incidence of ischemic infarct in FD vs. NFD as 20.1% vs. 0.48% while there was no difference in the incidence of hemorrhage in the two groups [18]. In our study the incidence of ischemic infarct in FD vs. NFD was 73% vs. 27% while the incidence of hemorrhage in the two groups was 20% vs. 60%.…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 38%
See 3 more Smart Citations